Nomuraea rileyi Inhibits growth and biofilm formation Xanthomonas citri subsp citri - Luján, Enrique Ernesto (2016)
Nomuraea rileyi ARSEF 4094, an entomopathogenic fungus (EF) isolated from Spodoptera frugiperda, produces secondary metabolites (SM) that interfere with the development of the insects that attack and bacteria from the insect body. It is known that the addition of insects into the fungal growth medium stimulates the production of SM. SM are known to affect bacterial growth in their planktonic and biofilm (BF) states. Therefore, the aim of this study was to evaluate the inhibitory capacity of N. rileyi in the presence of S. frugiperda on Xanthomonas citri subsp. citri (Xcc) growth and BF formation. This bacterium causes citrus canker, the main crop in Tucumán.EF was cultured in SMY medium with S. frugiperda and incubated at 28 °C during 15 days, at 180 rpm. Fungal and insect controls with the same treatment were made. Ethyl acetate extracts from biomass and supernatant from each condition were obtained. Xcc growth inhibition was determined by the microdilution method at 48 h and the inhibition of BF formation was quantified by a colorimetric method.The extract from fungal-insect biomass was the most efficient in inhibiting BF formation (38%), affecting Xcc growth in only 15%. While the extract from fungal biomass inhibited the growth of the bacteria in 32% and only 9% the formation of BF. According to this, the presence of insects could stimulate the production of SM, which interfere with the synthesis of BF.The results showed the potential use of extracts from N. rileyi as a natural strategy and environmentally acceptable for crop protection against diseases caused by pathogenic microorganisms.